Moderating Role of Audit Committee in Determinant Relationship with Audit Delay - Sylvia, Leny; Louw, Febriana (Jurnal Akuntansi, 2025)
Purpose – The objective of this study is to examine the moderating role of Audit Committee in the relation between determinants, which are Financial Distress, Complexity of Operation, and CPA Reputation, toward Audit Delay. Design/Methodology/Approach – Purposive sampling was applied in filtering research data from the financial statements of property and real estate companies registered on the Indonesia Stock Exchange during 2022-2024. A total of 160 financial statements from 73 issuers were analyzed after outlier adjustment. Data analysis was performed using Moderated Regression Analysis (MRA) with the SPSS 26 application. Results – This study found a positive influence of Financial Distress on Audit Delay. Whereas, Complexity of Operation and CPA Reputation do not have significant impact to Audit Delay. MRA analysis shows that the audit committee does not act as a moderator in the relationship between determinants with Audit Delay. Research limitations/Implications – The presence of Audit Committee in property and real estate issuers registered on IDX has not been effective enough because companies only consider the existence of Audit Committees as a means of complying with OJK regulations, thereby failing to accelerate the financial statement audit process. Practically, these findings highlight that managementand regulators need to strengthen the role and effectiveness of audit committees to ensure timeliness and enhance investor confidence in audited financial statements. Keywords: Audit Delay, Audit Committee, Complexity of Operation, CPA Reputation, Financial Distress